Ethiopia, Policies for Sustainable Land Management in the Ethiopian Highlands Dataset 1998-2000 - International Food Policy Research Institute (International Food Policy Research Institute, 2005)
This dataset contains aggregated data on financial, human, and institutional resources for agricultural research and development (R&D) at country, regional and global levels. Accurate, reliable, and internationally comparable quantitative information on investments, human capacity, and the institutional structure of agricultural R&D is fundamental to understanding the contribution of research to agricultural growth in low- and middle-income countries. Providing such data is the mission of IFPRI’s Agricultural Science and Technology Indicators (ASTI) program. Through its large network of national, regional, and international partners, ASTI collects and analyzes data from government, higher education, nonprofit, and (where possible) private-sector agencies involved in agricultural R&D. The program conducts ongoing analysis of these datasets; disseminates the results of this analysis to promote advocacy and support policymaking; and builds national and regional capacity for data collection and analysis.